Glial Tissue Mechanics and Mechanosensing by Glial Cells - Pogoda, Katarzyna; Janmey, Paul A. (Frontiers in Cellular Neuroscience, 2018)
Understanding the mechanical behavior of human brain is critical to interpret the role of physical stimuli in both normal and pathological processes that occur in CNS tissue, like development, inflammation, neurodegeneration, aging and most common brain tumors. Despite clear evidence that mechanical cues influence both normal and transformed brain tissue activity as well as normal and transformed brain cell behavior, little is known about the links between mechanical signals and their biochemical and medical consequences. The multi-level approach from whole organ rheology to single cell mechanics is needed to understand the physical aspects of human brain function and its pathologies. This review summarizes the latest achievements in the field.